KNOWLEDGE PRACTICE AND ATTITUDE OF NURSES RELATED TO PREVENTION COMPLICATIONS OF THE IV CANNULATION AT IMAM ALI HOSPITAL (KAP STUDY) - Hussin Batool kadham; Mohanned Abd Ali Essa (Scholar Express Journals, 2023)
Peripheral intravenous cannulation is one of the operations that junior nurse professionals perform the most frequently. Given this, it is crucial to comprehend the peripheral intravenous cannulation process (11) Intravenous cannulation has a significant risk of complications and may be challenging. The cannula is accompanied by problems and effects, such as superficial phlebitis and infiltration, that worsen the pain. It may cause further delays in treatment and transfer, possibly leading to unfavorable patient outcomes if the cannulation fails or is ignored (2)(5) method: The study aimed to assess nurses' knowledge, attitudes, and practice in avoiding problems following cannulation. 82 nurses who worked at Baghdad's Imam Ali Hospital between December 2022 and February 2023 were chosen as an acceptable sample. Data was gathered using a questionnaire form. Results: the great majority of participant's females (73.2), while the highest percentage was for the age group 36 and over, with 35.4, regarding the leve l of education, it was for the diploma certificate, 37.8 regarding years of work experience, and category 1-5 years A by 26.9. another side showed a medium association with knowledge and practices with a value of .513, Followed by a strong correlation among knowledge and attitudes with a value of 637. finally, the lowest value was weak between practices and attitude, with a value of 392. All coefficients are statistically significant at less than .005. there is a statistically significant association between the variables of age, gender, educational level, and years of experience and their knowledge, practice, and attitudes, with a significant level of less than 0.05. the Nurses with university education have a good level of knowledge, always application, and a positive attitude to prevent complications from cannulation. Recommendation: Implementing an educational program for nurses on the prevention and maintenance of cannulation. Taking into account the stimulating bumps and activating the role of the continuing education unit in hospitals to follow up on scientific developments.
Keywords: Cannulation; Complication; Nurses Knowledge; Intravenous